REVISITING THE CULTURAL IDENTITY OF NYADRAN IN THE GLOBALIZATION ERA: QUALITATIVE ANTHROPOLOGY PERSPECTIVE - Amal, Bakhrul Khair; Supsiloani, Supsiloani; Samosir, Sry Lestari; Moktar, Megan Riri (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
In an increasingly integrated and connected era of globalization, cultural identity becomes important in maintaining the diversity and uniqueness of each human group. This research changes the traditional cultural identity of